»Relationship Marketing for Future!« Leveraging Co-Responsibilization to Enhance Sustainability - Eggert, Andreas; Steinhoff, Lena; Alberternst, Benedikt; Kessing, Katharina; Schäfers, Tobias; Böhm, Eva; Garnefeld, Ina; Woisetschläger, David
In response to the escalating challenges posed by rising sea levels, increasing temperatures, and anthropogenic hazards like wildfires and flooding, it has become imperative for marketing researchers and practitioners to develop strategies to combat climate change. However, our observation underscores a prevailing trend in existing research, where responsibility is often shifted exclusively to either consumers (i.e., consumer responsibilization) or corporations (i.e., corporate social responsibility). To address this limitation, our interactive special session proposes co-responsibilization as an innovative relationship marketing strategy. This relational approach, bringing consumers and firms together in the quest to enhance sustainability, involves joint efforts in designing and engaging in sustainable business and consumption practices. Despite the potential of co-responsibilization, numerous questions persist regarding its implementation as a relationship marketing strategy, its effectiveness in fighting climate change, and its potential intended and unintended consequences for customer relationships. Against this backdrop, we propose this special session as a promising platform for inspiring fruitful research ideas and collaborations, ultimately promoting relationship marketing strategies for a more sustainable future. Specifically, our special session aims to achieve three objectives. First, we aim to promote the concept of co-responsibilization through relationship marketing strategies and instruments. Acknowledged experts will briefly illustrate co-responsibilized relationship marketing in their respective study contexts. These topic areas span business-to-business and business-to-consumer marketing, including industrial services, e-commerce, and loyalty programs. Second, we aim to collaboratively refine our concept of co-responsibilized relationship marketing and define promising paths for future research. To achieve this, we will employ a highly interactive format that features small-group research idea brainstorming and the creation of concept maps. Third, we hope that this session will lead to fruitful research collaborations. Given that questions on responsibilization have been addressed in other marketing subdisciplines (e.g., consumer culture theory), our session offers the potential to bring together scholars from different camps and develop boundary-spanning solutions to effectively combat climate change.